dRVVT Is more Sensitive than KCT or TTI for Detecting Lupus Anticoagulant Activity of Anti-β2-glycoprotein I Autoantibodies - Pengo, V.; Biasiolo, A.; Rampazzo, P.; Brocco, T. (Thrombosis and Haemostasis, 1999)
Anti-β2-glycoprotein I (β2-GPI) antibodies behave as classical Lupus Anticoagulants (LA), as they inhibit phospholipid-dependent coagulation reactions and their activity disappears in the presence of excess exogenous phospholipids (PLs). We have recently shown that a certain amount of PLs in the dilute Russell Viper Venom Time (dRVVT) test system is required to express LA activity of anti β2-GPI antibodies. We have now extended this observation to two other tests, i.e., Kaolin Clotting Time (KCT) in which PLs are not added, and Tissue Thromboplastin Inhibition test (TTI) in which PLs are extremely diluted. In fact, affinity-purified antibody preparations from 5 patients with antiphospholipid syndrome did not express or only weakly expressed anticoagulant activity in both tests; the mean ratios of coagulation times obtained with purified antibodies and that of control buffer were 1.11 and 1.0 for KCT and TTI, respectively. On the contrary, the mean ratios in dRVVT were 1.31 and 1.49 at a PLs dilution of 1:8 and 1:64, respectively. Therefore, the presence of LA activity due to autoantibodies to β2-GPI is characterized by a positive dRVVT and negative or only weakly positive KCT and TTI.